The great financial crisis : causes and consequences - Foster, John Bellamy; Magdoff, Fred, 1942- (New York : Monthly Review Press, 2009)
In the fall of 2008, the United States was plunged into a financial crisis more severe than any since the Great Depression. As banks collapsed and the state scrambled to organize one of the largest transfers of wealth in history, manyincluding economists and financial expertswere shocked by the speed at which events unfolded.In this new book, John Bellamy Foster and Fred Magdoff offer a bold analysis of the financial meltdown, how it developed, and the implications for the future. They examine the specifics of the housing bubble and the credit crunch as well as situate current events within a broader crisis of monopoly-finance capitalismone that has been gestating for several decades. It is the'real' productive economy? tendency toward stagnation, they argue, that creates a need for capital to find ways to profitably invest its surplus. But rather than invest in socially useful projects that would benefit the vast majority, capital has constructed a financialized'casino' economy that neglects social needs and, as has become increasingly clear, is fatally unstable. Written over a two-year period immediately prior to the onset of the crisis, this timely and illuminating book is necessary reading for all those who wish to understand the current situation, how we got here, and where we are heading.
Introduction -- The household debt bubble -- The explosion of debt and speculation -- Monopoly-finance capital -- The financialization of capitalism -- The financialization of capital and the crisis.
Koleksi Sumbangan : Dr. Syed Husin Ali
Includes bibliographical references (p. [141]-156) and index.
Keywords: Financial crises; Debt; Monopolies; Capitalism